The “Elementary Forms” of Mobile Communication: The Social Uses of the Mobile Phone Among Portuguese Adolescents - Lapa, T. (XIX ISA World Congress of Sociology, 2018)
This paper argues that is useful to adopt a Durkheimian cultural model to look at the functions or uses of the mobile devices by essentially looking at their capacity for normative and social integration or, on the contrary, to jeopardize these types of integration, when, for instance, they constitute a factor of individuation and segregation . Following this perspective, the basic units of analysis include the shared symbol but also the rite impregnated of meaning such as the exchange of messages or the mediated ritualistic forms in a media saturated society . For adolescents, personalized, distinctive and original uses of symbolic forms on the mobile phone can be a routine method of peer-sharing and support, a means of separating the “we” from the “others”, reinforcing an emotional attachment and the cohesion of a group that shares the same symbols, culture and domestication of mobile communication . However, they also bring the prospect of segregation . Despite recognized problems in functionalist approaches, their usefulness lies in the ability to interconnect cultural aspects with concrete social action . Therefore, it is argued that the Durkheimian model is profitable in media studies and it converges with the empirical results on the domestication of mobile devices among Portuguese teenagers . Albeit Giddens’ (1984) criticism of functionalist arguments within the social sciences, it is also argued that the Durkheim’s model is not inconsistent with the role of mobile devices in the maintenance of the ontological security of agents, and with the domestication approach in communication studies . For example, the breakdown of the moral order of permanent connectivity can cause disorientation when connection to mobile networks is no longer available . These perspectives, when applied to the study of mobile communication, all congregate in the same direction: they underline the emotional importance and consequences of mobile devices in teenagers’ daily life.